Industry Characteristics and Patterns of Sustainability Reports - Yavida Nurim; Eka Noor Asmara (Indonesian Journal of Sustainability Accounting and Management, 2019)
Since 2002, the Indonesian Government has encouraged listed and unlisted companies to disclose sustainability reports comprised of three performance indicators—economic, environmental, and social—as Global Reporting Initiatives (GRI) guidance. The main issue is that different industry characteristics have different orientations of sustainability reporting because of the differences between their main stakeholders. In fact, several GRI criteria do not match every industry characteristic. For example, banking does not report on materials, emissions, or pollution as part of their environmental performance. This research aims to identify the patterns of sustainability reporting from 2015 to 2016, based on industry characteristics. The study compares environmental and social performance reporting patterns of the manufacturing and financial sectors. Results show that manufacturers are more concerned with environmental performance while the financial sector is more concerned with social performance. This evidence contributes to the stakeholder theory and efforts in sustainability report modelling.